PEMANFAATAN APLIKASI TARTEEL DALAM MOTIVASI MUROJAAH SANTRI DI KELAS X MA - Fathimah Azzahra; Lestari, Anita (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Murajaah is an essential activity in maintaining the quality of Qur’anic memorization among students. However, in practice, students’ motivation to engage in murajaah often declines due to monotonous methods and a strong dependence on teacher guidance. This condition highlights the need for instructional innovation through the integration of digital technology. This study aims to describe the use of the Tarteel application in motivating murajaah activities among eleventh-grade Madrasah Aliyah students. This study employed a qualitative approach using Classroom Action Research (CAR). The research participants were eleventh-grade students enrolled in a Qur’anic murajaah program at a Madrasah Aliyah. Data were collected through observation, interviews, and documentation over a two-week implementation period. Qualitative data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that during the initial stage of using the Tarteel application, students began to show interest in technology-based learning media, particularly due to the immediate feedback features on recitation errors. However, this initial interest did not lead to a significant improvement in students’ motivation for murajaah. In the subsequent stage, although the use of the application was implemented in a more structured and scheduled manner, students’ murajaah motivation remained relatively stable. There were no substantial changes in the frequency of murajaah, recitation quality, self-confidence, or daily murajaah habits. Students continued to feel more comfortable submitting their recitation directly to teachers rather than using the application. In conclusion, the Tarteel application functions as a technical support tool in murajaah activities but has not been able to significantly enhance students’ murajaah motivation without stronger pedagogical strategies and sustained teacher guidance.